Identification of Hypoxia–Immune-Related Gene Signatures and Construction of a Prognostic Model in Kidney Renal Clear Cell Carcinoma - Bai, Shuheng; Chen, Ling; Yan, Yanli; Wang, Xuan; Jiang, Aimin; Li, Rong; Kang, Haojing; Feng, Zhaode; Li, Guangzu; Ma, Wen; Zhang, Jiangzhou; Ren, Juan (Frontiers in Cell and Developmental Biology, 2022)
Introduction: Kidney renal clear cell carcinoma (KIRC), a kind of malignant disease, is a serious threat to public health. Tracking the information of tumor progression and conducting related dynamic prognosis model are pretty necessary for KIRC. Considering the interaction of immune and hypoxia influences the prognosis of patients with KIRC, it is crucial to identify hypoxia-immune-related genes and construct a prognostic model. Methods: The hypoxia status and immune status of KIRC patients were identified by utilizing t-SNE and ImmuCellAi for gene expression data. The COX and Lasso regression were used to identify some hypoxia-immune-related signature genes and construct a prognostic risk model based on these genes. Then internal and external validation were also conducted for the construction of a prognostic model. Finally, some potentially effective drugs were screened by Cmap dataset. Results: We found that high-hypoxia status and low-immune status tend to induce poor overall survival (OS). Six genes, including PLAUR, UCN, PABPC1L, SLC16A12, NFE2L3, and KCNAB1, were identified and involved in our hypoxia-immune-related prognostic risk model. Internal verification showed that this constructed model's area under the curve (AUC) values for 1-, 3-, 4- and 5-year OS were 0.768, 0.754, 0.775, and 0.792, respectively. For external verification, the AUC for 1-, 3-, 4- and 5-year OS were 0.768, 0.739, 0.763 and 0. 643 respectively. Meanwhile, the decision curve analysis (DCA) analysis presented excellent clinical effectiveness. Finally, we found that four drugs (including vorinostat, fludroxycortide, oxolinic acid and flutamide) might imply great possibility to alleviate or even reverse the status of severe hypoxia and poor infiltration of immune cells. Conclusion: Our constructed prognostic model based on hypoxia-immune-related genes has excellent value of effectiveness and clinical application. Moreover, some small-molecular-drugs are screened that may alleviate severe hypoxia and poor infiltration of immune cells.